The Authority of the Regional Head in the Dismissal of State Civil Servants Based on a Court Decision That Has Permanent Legal Force - Mokoginta, Sofian Wijaya; Djafar, Marwan; Beddu, Sumiyati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the authority of regional heads in dismissing State Civil Apparatus (ASN) in South Bolaang Mongondow Regency based on court decisions that have permanent legal force (inkracht). This study is important considering that regional heads have a strategic role in fostering regional personnel, but the exercise of their authority in terms of dismissal of ASN often raises legal problems, especially when dealing with a final and binding court decision. This study uses a normative juridical method with a legislative approach and case studies in the area. The results of the study show that normatively, regional heads have a clear legal basis to dismiss civil servants who have been sentenced to criminal offense based on court decisions that have been inkracht, as stipulated in Law Number 5 of 2014 concerning the State Civil Apparatus and its implementing regulations. However, in South Bolaang Mongondow Regency, the implementation of these authorities still faces challenges, such as inconsistencies in regulatory interpretations, political interventions, and lack of understanding of the general principles of good governance (AUPB). Therefore, legal certainty, strict technical guidelines, and stronger supervision are needed so that the authority of regional heads in dismissing ASN is truly carried out professionally, objectively, and fairly.